Nondestructive quantification of single crystal elasticity for additively manufactured SB-CoNi-10C, IN625, and Ti64. (April 2023) - Rossin, Jeff; Leser, Patrick; Benzing, Jake T.; Torbet, Chris; Dillon, R. Peter; Smith, Stephen; Daly, Samantha; Pollock, Tresa M.
Abstract: Resonant ultrasound spectroscopy (RUS) is capable of determining the single crystal elastic constants from polycrystalline specimens with known crystallographic texture. However, the calculated single crystal elastic constants vary with the measured texture, resulting in inconsistent estimates for additively manufactured (AM) specimens with heterogeneous texture regions. In this work, the accuracy of the determined single crystal elastic constants is improved by incorporating the uncertainty of the texture in the determination of single crystal elasticity, and requiring only small quantities of electron backscatter diffraction data (EBSD) to do so. The single crystal elastic constants are determined by Bayesian inference with parallelized sequential Monte Carlo (SMC), enabling an order of magnitude reduction in computational cost. AM specimens of a cobalt-nickel-base superalloy (SB-CoNi-10C) demonstrate that the incorporation of texture variability enables the single crystal elastic constants to converge to the reported literature values within one standard deviation, avoiding any dependence on the initial texture values. The single crystal elastic constants of nickel-base-superalloy Inconel 625 (IN625) and Ti-6Al-4V (Ti64) are determined from AM specimens, using only RUS and EBSD data. The determined single crystal elastic constants of IN625 agree between two different texture conditions (induced by AM raster strategy), as well as with the literature values, within one standard deviation. The single crystal elastic constants determined from three AM Ti64 specimens, printed with different beam powers, agree with the range of literature values within two standard deviations but demonstrate variability between AM specimens, indicating that the frequencies may be susceptible to the effects of secondary phases.